Identification of the nonclassical HLA molecules, mica, as targets for humoral immunity associated with irreversible rejection of kidney allografts. - Sumitran-Holgersson, S; Wilczek, H; Holgersson, J; Söderström, K (2002)
BACKGROUND: A substantial portion of kidney allografted patients experience early acute rejection episodes and even irreversible rejections in the early posttransplantation period. The presence of HLA alloantibodies before grafting is associated with early immunological complications, but in many patients rejections and graft loss occur even in the absence of such antibodies. METHODS: In this study, 748 serum samples taken before and at various time points after kidney transplantation from 139 patients were investigated for the presence, frequency, and specificity of kidney microvascular endothelial cell (KMEC)-reactive antibodies using major histocompatability class (MHC) I-related chain A (MICA) transfected cells and flow cytometry, antibody blocking experiments, and Western blotting. The ability of MICA-specific antibodies to fix complement and to induce a prothrombotic phenotype in KMECs was investigated. RESULTS: A polymorphic, 62 kDa nonclassical HLA class I molecule is identified as a new target molecule for reactivity in sera from patients with irreversible rejections. Specific blocking and transfection experiments verified the target molecule as MICA. A significant correlation was established for pre- or posttransplantation MICA humoral immunity and graft loss (P<0.001). MICA-specific antibody titers increased in the posttransplantation period and were present before any signs of clinical rejection. MICA antibody-containing patient sera induced a prothrombotic phenotype in KMECs. CONCLUSION: The increasing polymorphism detected at the MIC loci combined with the results of this study suggest that typing for the MIC loci and crossmatching for the detection of anti-MIC antibodies before transplantation should be used routinely. A better recipient-donor selection based on a negative crossmatch for both anti-donor HLA and MICA antibodies will decrease early graft rejections and losses.